Writing Procedure Texts Through â€œHow To Makeâ€¦â€ Video - Siti Nur Aisah (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
ABSTRACT: The aim of this research is to describe whether there is effect in teaching writing procedure text for 7th grade students of SMP Al-Fattah Buduran Sidoarjo. The instrument to collect the data was test. After collected the data, the researcher analyzed it. The analysis of data were from pre test and post test score of experimental and control class. The result of the research showed that the mean score of experimental class higher than the mean of control class (83 > 69.07) and the t-test result showed the value of t-test is higher than the value of t-table. The value of t-test was 6.163 while the value of t-table on Î± = 5% was 1.699. It indicated that the hypothesis of this research was accepted. For the next researcher, hope this research can be alternative method for teaching writing procedure text through video.